Demand and supply side factors for accelerating varietal turnover: An evidence from soybean in India - Nuthalapati, Chandra Sekhara Rao; Sonkar, Vinay Kumar; Kumar, Anjani (International Food Policy Research Institute, 2020)
Soybeans were promoted on a large scale in India in order to augment farmers’ incomes in poverty-stricken areas and to combat dietary protein deficiencies. Soybean cultivation in India is a unique success story, having expanded in area from zero in 1970 to 11.5 million hectares by the first decade of this millennium At this juncture, the major concern of policymakers is to sustain cultivation of soybeans by ensuring reasonable growth in yield and farm incomes in the face of competitive yield improvements in comparable crops such as corn. This paper tries to understand the varietal adoption patterns and the stages of diffusion of existing varieties. It uses a large primary data set of 1,410 farm households in central and western India to unravel the underlying pathways for accelerating varietal turnover. It employs a dynamic framework by harnessing duration analysis. The average age of the adopted varieties is 8.4 years, which is relatively high and implies slower varietal turnover. Survival functions show that adoption of the leading varieties has reached the saturation stage and that policy intervention at this point can thus have a rapid impact in terms of varietal replacement. The analysis of rate of change of varietal replacement through hazard functions throws up interesting conclusions that are relevant to the formulation of new policies. Examination of all three conceptualized pathways—farm characteristics, sources of information, and perceived traits of the varieties and of genetic improvements—suggest the need for substitution of existing varieties with new improved varieties. While the drivers of varietal change do not vary with size of farm, regional differences are relevant. This paper discusses the potential impact of policy on production and income.